Conhecimento sobre urgências e emergências médicas de discentes e docentes da Faculdade de Odontologia da Universidade Federal do Amazonas (FAO/UFAM) - Nogueira, Luiz Gustavo de Souza (2022)
In a dental environment, care for the elderly, longer appointments, the use of different medicines to treat systemic diseases, anxiety and fear are examples of factors that can trigger medical urgencies and/or emergencies (MUEs). They can affect any individual, before, during or after the appointments. Therefore, the dentist must be prepared to overcome these situations from prevention to facing the event. This study aims to evaluate the level of knowledge about MUEs in Dentistry among professors and students of the Faculty of Dentistry of the Federal University of Amazonas (FAO-UFAM). The data were collected through an online questionnaire with 15 multiple-choice questions about syncope and lipothymia, seizures, hypoglycemia, airway obstruction, cardiorespiratory arrest and anaphylactic shock to be answered by the target population. The questionnaire was answered in full and individually for further analysis and statistical treatment performed by the researchers. The sample consisted of 115 volunteers, most of whom were students (89.57%), female (71.3%), enrolled in the seventh period of the Faculty of Dentistry of the Federal University of Amazonas (36.89%). The mean of correct answers from professors was 64.39% and median 75% and from students the mean was 54.19% and median 66.02%. These rate averages make it possible to grade the knowledge of each academic group as good. The review of this knowledge and future training are necessary among professionals and students.